Case of successful treatment of widespread abdominal actinomycosis - O. P. Kozlova; A. K. Mirzabalaeva; R. M. Chernopyatova; V. A. Zinzerling; F. Y. Ambalova; I. V. Sergeeva; R. S. Gorgidjanian; N. N. Klimko (Журнал инфектологии, 2014)
.